ANALISIS KUALITAS LAYANAN BUKA LAPAK DALAM MEMPENGARUHI PENGAMBILAN KEPUTUSAN BERBELANJA DI BUKA LAPAK - HANNA MEILANI DAMANIK (JURNAL ILMIAH MAKSITEK, 2020)
This study analyze the influenced of service quality to buying decisions. The purpose of this research is to see the effect of the service quality, consumer purchase intention and buying decisions at Buka Lapak . This study using snowball sampling metods and analyzed by path analysis. The result show that service quality has a significant effect on buying decisions which are moderated by purchase intention . The purchase intention will be increase if we serve better and better and the other hand purchase intention will drive the consumer’s buying decision at Buka Lapak